Non-isocyanate polyurethane/epoxy hybrid materials with different and controlled architectures prepared from a CO2-sourced monomer and epoxy via an environmentally-friendly route. Issue 46 (31st May 2017) - Ke, Jiexi; Li, Xiaoyun; Wang, Feng; Jiang, Shuai; Kang, Maoqing; Wang, Junwei; Li, Qifeng; Wang, Zhijie
Abstract : A series of polyurethane/epoxy hybrid materials with different and controlled architectures were prepared by a non-isocyanate route. The properties and architectures of materials were regulated by adjusting the ratio and type of amine. Abstract : Polyurethane/epoxy hybrid materials from CO2 -sourced monomer were prepared via an environmentally-friendly and non-toxic route, which avioded the use of toxic isocyanate. A series of non-isocyanate polyurethane (NIPU)/epoxy hybrid materials, with different and controlled architectures, were synthesized from CO2, polypropylene glycol diglycidyl ether (PPGDGE), amines and diglycidyl ether of bisphenol-A (BADGE). Around 12 wt% CO2 was incorporated into PPGDGE to form a five-membered cyclic carbonate (5CC-PPGDGE). The complete conversion and selectivity of PPGDGE were obtained. The kinetics of 5CC-PPGDGE was investigated by reacting it with 1, 2-ethylenediamine (EDA) at different temperatures. NH2 -terminated pre-polymers were obtained by reacting 5CC-PPGDGE with various excessive amines. Finally, the hybrid materials were obtained by curing pre-polymers with BADGE. The results showed that a high content of amine with more functional groups led to better mechanical performances than diamine-based hybrid materials. This is the first time that architectures have been controlled by altering the amine ratio and functionality. And these hybrid materials exhibited satisfactory mechanical performances. The DETA-based and TETA-based materials with high amine ratio exhibited a tensile strength of 15.0 MPa and 12.5 MPa, accompanied with elongation at break of 151.3% and 170.9%, respectively. The gel content, glass transition temperature and thermodynamic stability went up first and then declined with the increase of amine ratio, which demonstrated the architectures of hybrid materials ranged from defective to cross-linked and linear structures.